Fusion of Infrared and Visible Images Based on Non-subsample Contourlet Transform - Tingman Zhang; Qing Wang (Universitas Ahmad Dahlan, 2016)
For the single spectrum image could not fully express the target feature information, this paper proposed a multispectral image fusion method based on non-subsample contourlet transform (NSCT). For the low frequency coefficients decomposed, fourth-order correlation coefficient is used to calculate the correlation between each low frequency coefficients, averaging fusion for the higher correlation coefficient, weight phase congruency fusion for the low correlation coefficient. For high frequency coefficients, Gaussian weight sum modified Laplace method is used for fusing, to retain more local structure details. Simulation results show that the method effectively retain the image structure information and more local details, and increase the image contrast.